HISTORY OF TRICKING FOUNDATION AS AN EXTREME SPORT AND ITS DISTRIBUTION ASPECTS IN UKRAINE - Tetiana Hnitetska; Lidiia Zavatska; Oleksandra Holub (Lesya Ukrainka Volyn National University, 2017)
Relevance. Many people associate tricking with capoeira, acrostreet, eXtreme Martial Arts and Multi Level Moves. But, it's the single extreme sport, ideas of foundation and distribution of which in Ukraine are studied insufficiently. The aim of the study is - to study the peculiarities of the tricking foundation as an innovative kind of extreme sports and investigate the historical aspects of its foundation and distribution in Ukraine, in particular, in Volyn region. Results of the study. Establishment of tricking took place at USA in 60th years of XX century. It`s movement base was created by extreme sportsmen Ernie Reyes, Mike Chaturantabut, Daniel Sterling, Matt Emig and others. Establishment of tricking in Ukraine starts at 2009 and related to the All-Ukrainian youth association «Astorun» (head - Roman Konopatskyi, BilaTserkva). Today there more than 10 tricking teams in Ukraine, the most known are «VIATORES» (Lviv, 2013), «Nation Motion» (Cherkasy, 2014), «ASTIR» (Rivne, 2012), tricking schools in Mykolaiv, Kyiv, Kharkiv and others. At Volyn region tricking was established in 2010-2012 at traceurscommunit, and at 2012 was created sports organization «TWIST FREERUN FAMILY» (Lutsk). Conclusions. Tricking, after its establishment in 60th years of XX century in USA, today become very popular all over the world. In Ukraine tricking was founded in first 10th of XXI century and still is in developmental phase.